COVID-19 Reverse Prediction and Assessment on the Diamond Princess Cruise Ship - Zhang, Juan; Sun, Gui-Quan; Li, Mingtao; Gao, Rui; Ren, Huarong; Pei, Xin; Jin, Zhen (Frontiers in Physics, 2020)
As of July 21, 2020, the coronavirus SARS-CoV-2 had spread to almost all countries around the world and caused more than 14.8 million confirmed cases, owing to its high transmissibility and fast rate of spread. Of the infected locations, the Diamond Princess cruise ship is special in that it is an isolated system with a population highly concentrated in a limited space, providing particularly favorable conditions for the transmission of the novel coronavirus-associated pneumonia, COVID-19. The Japanese government's emergency measures for controlling the spread of COVID-19 on the cruise ship have also been questioned. In this paper we develop a homogeneous mixed difference system to describe the mechanism of transmission of COVID-19 on the cruise ship, reverse-predict the epidemic transmission trend from January 20 to February 20, 2020, including the daily number of infected people and the peak time of infection, estimate the range of the basic reproduction number of virus transmission on the cruise ship, and assess the effects of prevention and control measures. It is concluded that the isolation of people, along with rapid and comprehensive detection of infections, play an important role in controlling the epidemic. In fact, the Japanese government's emergency measures did have a certain effect on limiting the spread of COVID-19, but the number of infected people could have been reduced by at least 60% if all personnel on the cruise ship had been tested and isolated promptly as early as February 5.